The Influence of Product Quality, Brand Image on Purchase Decisions and Brand Trust as Mediation Variables (Study on iPhone Users in Malang City) - Nurmalita Sari; Sudarmiatin; Titis Shinta Dhewi (CV. AFDIFAL MAJU BERKAH, 2022)
Smartphone users in Indonesia are ranked among the countries with the most users in the world. The decision to buy a smartphone is inseparable from product quality, brand image, and brand trust in smartphone products. This study aims to determine the direct and indirect effect of product quality, brand image on purchase decisions, and brand trust on iPhone users in Malang. This study uses a descriptive explanatory quantitative approach. The sampling technique used purposive sampling totaling 250 respondents. Data analysis of this research was carried out using the Partial Least Square (PLS) method using WarpPLS 7.0 software. The results show that: 1) product quality has a direct positive and significant effect on brand trust & purchase decisions 2) brand image has a direct positive and significant effect on brand trust & purchase decisions 3) brand trust has a direct positive and significant effect on purchase decisions 4) product quality has a positive and significant effect on purchase decisions through brand trust. 5) brand image has a positive and significant effect on purchase decisions through brand trust. Based on the results of this study, the researchers suggest that this research is not only one product, so it can be generalized widely